2017
DOI: 10.1080/21645515.2017.1363935
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles as an efficient nanoplatform for the delivery of therapeutics

Abstract: Extracellular vesicles (EVs) are membrane-derived vesicles that are enriched with RNAs, proteins and other functional molecules. We exploit the unique physical properties of EVs as a promising and advantageous nanoplatform for the delivery of therapeutic drugs and genetic materials. Early successes in the discovery of various disease-related characteristics of EVs have driven a new wave of innovation in developing nanoscale drug-delivery systems (DDSs). Nevertheless, there are several issues that need to be co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 119 publications
0
21
0
Order By: Relevance
“…For example, mesenchymal stromal cells (MSCs) can acquire strong anti-tumor activity after priming with paclitaxel (PTX) because MSCs secrete a high amount of membrane microvesicles that will contain the drug [ 75 ]. Another study reported how melanoma cells can be loaded with survivin T34A and gemcitabine to produce exosomes that carry the drug to treat pancreatic adenocarcinoma [ 76 ]. Doxorubicin and methotrexate have been loaded into tumoral cells and their apoptotic bodies containing the drug have been used to kill tumor cells, with reduced side effects [ 77 ].…”
Section: Engineered Evsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, mesenchymal stromal cells (MSCs) can acquire strong anti-tumor activity after priming with paclitaxel (PTX) because MSCs secrete a high amount of membrane microvesicles that will contain the drug [ 75 ]. Another study reported how melanoma cells can be loaded with survivin T34A and gemcitabine to produce exosomes that carry the drug to treat pancreatic adenocarcinoma [ 76 ]. Doxorubicin and methotrexate have been loaded into tumoral cells and their apoptotic bodies containing the drug have been used to kill tumor cells, with reduced side effects [ 77 ].…”
Section: Engineered Evsmentioning
confidence: 99%
“…Doxorubicin and methotrexate have been loaded into tumoral cells and their apoptotic bodies containing the drug have been used to kill tumor cells, with reduced side effects [ 77 ]. Cells have been loaded with NPs also— superparamagnetic iron oxide nanoparticles (SPIONs) have been loaded in mesenchymal stem cells to produce charged EVs to treat leukemia [ 76 ], while iron oxide NPs and a photosensitizer have been encapsulated in HUVECs and human macrophages to obtain EVs to treat prostate and cervical cancer, respectively [ 78 , 79 ]. Gene therapy can also be carried out with this approach—for example, mesenchymal stem cells have been loaded with different miRNAs to obtain EVs [ 80 ].…”
Section: Engineered Evsmentioning
confidence: 99%
“…HOC313-LM exosomes transferred oncogenic miR-343-3p and miR-1246 to HOC313-P cells and resulted in increase in cell motility and invasive ability [30] Cisplatin resistant OSCC cell lines (HSC3, SCC9) Parental OSCC (HSC3 and SCC9) EVs released from cisplatin-resistant OSCC cells transmit miR-21 to induce cisplatin resistance of OSCC cells [31] OSCC line (HSC3) Oral keratinocytes (RT7) OSCC derived EGFR-containing EVs were able to transform RT7 cells, effects of which were largely blocked by cetumixab [32] OSCC lines (Ca1 CALH2, SQCC/Y1) Premalignant buccal oral keratinocyte (SVpgC2a)…”
Section: Studymentioning
confidence: 99%
“…Increasing evidence shows that EVs are closely involved in the migration and metastasis of malignant tumors . As lipid membrane‐enclosed nanoparticles, the size of EVs is about 30–1000 nm . Therefore, taking advantage of EVs to deliver TRAIL is a promising way to improve the biological behavior of TRAIL .…”
Section: Nanotrail Treatment In Preclinical Researchmentioning
confidence: 99%